Cell penetrating peptide modulation of membrane biomechanics by Molecular dynamics. (17th May 2018) - Grasso, Gianvito; Muscat, Stefano; Rebella, Martina; Morbiducci, Umberto; Audenino, Alberto; Danani, Andrea; Deriu, Marco A.
Abstract: The efficacy of a pharmaceutical treatment is often countered by the inadequate membrane permeability, that prevents drugs from reaching their specific intracellular targets. Cell penetrating peptides (CPPs) are able to route across cells' membrane various types of cargo, including drugs and nanoparticles. However, CPPs internalization mechanisms are not yet fully understood and depend on a wide variety of aspects. In this contest, the entry of a CPP into the lipid bilayer might induce molecular conformational changes, including marked variations on membrane's mechanical properties. Understanding how the CPP does influence the mechanical properties of cells membrane is crucial to design, engineer and improve new and existing penetrating peptides. Here, all atom Molecular Dynamics (MD) simulations were used to investigate the interaction between different types of CPPs embedded in a lipid bilayer of dioleoyl phosphatidylcholine (DOPC). In a greater detail, we systematically highlighted how CPP properties are responsible for modulating the membrane bending modulus. Our findings highlighted the CPP hydropathy strongly correlated with penetration of water molecules in the lipid bilayer, thus supporting the hypothesis that the amount of water each CPP can route inside the membrane is modulated by the hydrophobic and hydrophilic character of the peptide. Water penetration promoted by CPPs leads to a local decrease of the lipid order, which emerges macroscopically as a reduction of the membrane bending modulus.